Evaluating the "Gradual Entrainment Lake Inverter" (GELI) artificial mixing technology for lake and reservoir management. (3rd July 2018) - Smith, Colin A.; Read, Jordan S.; Vander Zanden, M. Jake
ABSTRACT: Smith CA, Read JS, Vander Zanden MJ. 2018. Evaluating the "Gradual Entrainment Lake Inverter" (GELI) artificial mixing technology for lake and reservoir management. Lake Reserv Manage. 00:00–00. Thermal stratification is important to the structure and function of lake and reservoir ecosystems. Yet when lakes undergo eutrophication, thermal stratification can exacerbate water quality problems. As a result, lake management has sometimes involved artificial mixing and destratification, though the available technologies are few and costly. It is therefore important to test the efficacy of new technologies when they arise. Here, we evaluate a lake mixing technology, the "Gradual Entrainment Lake Inverter" (GELI), which was used to mix Crystal Lake, Wisconsin, a 34 ha, 21 m deep, dimictic lake during the summer months of 2012 and 2013. To assess the effect of the GELI treatment on thermal regime, we used DYRESM to model thermal conditions in the 2 treatment years but in the absence of treatment. We found GELI treatment slowly reduced stratification and the temperature range of the lake to 4.2 and 5.3 C in each treatment year, on average. Full destratification and oxygenation of the water column prevented fall hypoxia and anoxia. We found efficiency of the GELI averaged 1.9% during treatment, which is higher than efficiencies reported from field applications of bubble plume aeration. We used DYRESM to simulate bubble plume aeration to match the observed destratification from our GELI treatment and estimate aeration would have required 1.4–1.8 times the airflow and power costs of the GELI. Though considerable limitations of the current iteration of this technology exist, these may be reduced in future versions, possibly leading to a practical lake and reservoir management tool.